Impact of Municipal, Road Traffic, and Natural Sources on PM10: The Hourly Variability at a Rural Site in Poland - Mach, Tomasz; Rogula-Kozłowska, Wioletta; Bralewska, Karolina; Majewski, Grzegorz; Rogula-Kopiec, Patrycja; Rybak, Justyna (Energies (Basel), 2021)
The paper presents data from a monthly campaign studying the elemental composition of PM10, as measured by a specific receptor in Kotórz Mały (Opole Voivodeship)—located in the vicinity of a moderately inhabited rural area—measured in one-hour samples using a Horiba PX-375 analyzer. The hourly variability of SO2, NO, NO2, CO, and O3 concentrations, as well as the variability of meteorological parameters, was also determined. On average, during the entire measurement period, the elements related to PM10 can be arranged in the following order: As < V < Ni < Pb < Cr < Mn < Cu < Ti < Zn < K < Fe < Ca < Al < Si < S. Trace elements, including toxic elements—such as As, V, Ni, Pb, Cr, and Mn—were present in low concentrations, not exceeding 10 ng/m3 (average daily value). These elements had fairly even concentrations, both daily and hourly. The concentrations of the main elements in the PM10, as measured by the receptor, are subject to strong hourly changes related not only to changes in the structures of the sources identified in the statistical analysis, but also to wind speed and direction changes (soil and sand particle pick-up and inflow of pollutants from coal combustion). It has been shown that the transport emissions measured by the receptor can have an intense effect on PM10 in the afternoon.